H-CRRETAWAC-OH, a Lead Structure for the Development of Radiotracer Targeting Integrin α5β1?. (13th October 2014) - Haubner, Roland; Maschauer, Simone; Einsiedel, Jürgen; Eder, Iris E.; Rangger, Christine; Gmeiner, Peter; Virgolini, Irene J.; Prante, Olaf
Abstract : Imaging of angiogenic processes is of great interest in preclinical research as well as in clinical settings. The most commonly addressed target structure for imaging angiogenesis is the integrin αv β 3 . Here we describe the synthesis and evaluation of [ 18 F]FProp-Cys * -Arg-Arg-Glu-Thr-Ala-Trp-Ala-Cys * -OH, a radiolabelled peptide designed to selectively target the integrin α 5 β 1 . Conjugation of 4-nitrophenyl-( RS )-2-[ 18 F]fluoropropionate provided [ 18 F]FProp-Cys * -Arg-Arg-Glu-Thr-Ala-Trp-Ala-Cys * -OH in high radiochemical purity (>95%) and a radiochemical yield of approx. 55%. In vitro evaluation showed α 5 β 1 binding affinity in the nanomolar range, whereas affinity to αv β 3 and αIIb β 3 was >50  μ M. Cell uptake studies using human melanoma M21 ( αv β 3 -positive and α 5 β 1 -negative), human melanoma M21-L ( αv β 3 -negative and α 5 β 1 -negative), and human prostate carcinoma DU145 ( α v β 3 -negative and α 5 β 1 -positive) confirmed receptor-specific binding. The radiotracer was stable in human serum and showed low protein binding. Biodistribution studies showed tumour uptake ranging from 2.5 to 3.5% ID/g between 30 and 120 min post-injection. However, blocking studies and studies using mice bearing α 5 β 1 -negative M21 tumours did not confirm receptor-specific uptake of [ 18 F]FProp-Cys * -Arg-Arg-Glu-Thr-Ala-Trp-Ala-Cys * -OH, although this radiopeptide revealed high affinity and substantial selectivity to α 5 β 1 in vitro. Further experiments are needed to study the in vivo metabolism of this peptide and to develop improved radiopeptide candidates suitable for PET imaging of α 5 β 1 expression in vivo.